ISLAMIC CULTURAL HISTORY AS A LIFE PARADIGM - Yuyun Yunita; Muhammad Ali; Novita Herawati (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state . Character is the universal valuesof human behavior that includes all human activities, both in the context of relating to God, with oneself, with fellow humans, as well as with the environment, which are manifested in thoughts, attitudes, feelings, words, and actions based on norms. Religious norms, laws, etiquette, culture, and customs of Madrasas play a role in producing students who are smart in science, but also in character and personality. Through the example of Islamic figures and scholars discussed in Islamic Cultural History learning, especially the patience, persistence, and fortitude of the Prophet Muhammad SAW, his companions, scholars, and great figures in Islam so that some characters are built for students such as: religious, honest, disciplined, responsible, independent, social care and hard work.